CORPORATE GOVERNANCE DAN KINERJA PERUSAHAAN - Nazaruddin, Ietje (Universitas Muhammadiyah Yogyakarta, Indonesia, 2008)
This research try to explore wether the good corporate governance system related to corporate performance. Sample this study are companies listed in the Indonesia Stock Exchange. This research find that good corporate governance no relationship to firm performance and value. Result study not significant may be implementation the good corporate governance still new in Indonesia and than the effect nothing clear.